The Effect of using Chain Game toward Students’ Speaking Skill - Cahyani Octavia; Rosmania Rima; Dhafid Wahyu Utomo (Journal of English Language Teaching and Cultural Studies, 2023)
This research was aimed to find out the effect of using chain game toward students’ speaking skill. The quasi-experimental with nonequivalent control group design was applied in this study. The seventh grade students of SMP Negeri 17 Kota Serang as the population. The samples were 30 students of VII C as the experimental class which is treated by using chain game and 30 students of VII A as the control class which is treated without using chain game. The data came from an oral test that was divided into two parts: pre-test and post-test. After collecting the data, the researchers used statistical computation to analyze the data. The result showed that there was significant effect of using chain game towards students’ speaking skill. It can also be seen from the calculation using an independent sample t test. The t test value was 3.966 and the significance value was 5% of t table df = 56, which was 1.673. So, t observed was higher than t table (3.966 > 1.673). Hence, this research could be used as a reference for teaching speaking with chain game since the use of chain game was effective for teaching speaking to the seventh grade students at SMP Negeri 17 Kota Serang. Keywords: chain game; students’ speaking skill; teaching speaking